Characterization of White Matter Hyperintensities in Large-Scale MRI-Studies - Frey, Benedikt M.; Petersen, Marvin; Mayer, Carola; Schulz, Maximilian; Cheng, Bastian; Thomalla, Götz (Frontiers in Neurology, 2019)
Background White matter hyperintensities of presumed vascular origin (WMH) are a common finding in elderly people and a growing social malady in the ageing western societies. As a manifestation of cerebral small vessel disease, WMH are considered to be a vascular contributor to various sequelae such as cognitive decline, dementia, depression, stroke as well as gait and balance problems. While pathophysiology and therapeutical options remain unclear, large-scale studies have improved the understanding of WMH, particularly by quantitative assessment of WMH. In this review, we aimed to provide an overview of the characteristics, research subjects and segmentation techniques of these studies. Methods We performed a systematic review according to the PRISMA statement. 1196 potentially relevant articles were identified via PubMed search. Six further articles classified as relevant were added manually. After applying a catalogue of exclusion criteria, remaining articles were read full-text and the following information was extracted into a standardised form: year of publication, sample size, mean age, the cohort included, and segmentation details like the definition of WMH, the segmentation method, reference to methods papers as well as validation measurements. Results Our search resulted in the inclusion and full-text review of 137 articles. 134 of them belonged to 37 prospective cohort studies. Median sample size was 1030 with no increase over the covered years. 80 studies investigated in the association of WMH and risk factors. Most of them focussed on arterial hypertension, diabetes mellitus type II and Apo E genotype and inflammatory markers. 63 studies analysed the association of WMH and secondary conditions like cognitive decline, mood disorder and brain atrophy. Studies applied various methods based on manual (3), semi-automated (57) and automated segmentation techniques (75). Only 18% of the articles referred to an explicit definition of WMH. Discussion The review yielded a large number of studies engaged in WMH research. A remarkable variety of segmentation techniques was applied, and only a minority referred to a clear definition of WMH. Most addressed topics were risk factors and secondary clinical conditions. In conclusion, WMH research is a vivid field with a need for further standardisation regarding definitions and used methods.